2016
DOI: 10.1155/2016/4070635
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Levels and Vitamin D Supplement in Adult Patients with Asthma Exacerbation

Abstract: Introduction. Vitamin D deficiency has been linked to an increased risk of asthma exacerbations. Objective. This study aimed to compare vitamin D status during the period of severe asthma exacerbations and investigate if vitamin D supplementation improves asthma control. Methods. A total of 47 asthmatic patients and 40 healthy subjects participated in this study. Serum 25-hydroxyvitamin D (25(OH)D), asthma control test (ACT) score, and % predicted peak expiratory flow rate were evaluated in the period with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Brehm et al ( 18 ) found that 25-(OH) D 3 can exert a regulatory effect and affect the development of Th cells only when binding to VDR. Boonpiyathad et al ( 19 ) established the lipopolysaccharide-induced asthma model using VDR-knockout mice and wild-type mice, and found that the lung inflammation and asthma symptoms of VDR-knockout mice are not significant compared with those of wild-type mice. In this study, the correlations of VDR expression level in asthma patients with inflammatory factors were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Brehm et al ( 18 ) found that 25-(OH) D 3 can exert a regulatory effect and affect the development of Th cells only when binding to VDR. Boonpiyathad et al ( 19 ) established the lipopolysaccharide-induced asthma model using VDR-knockout mice and wild-type mice, and found that the lung inflammation and asthma symptoms of VDR-knockout mice are not significant compared with those of wild-type mice. In this study, the correlations of VDR expression level in asthma patients with inflammatory factors were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is key to the metabolism of calcium and phosphorus. In adults with Asthma, normal vitamin D levels correlated with improved asthma control and therefore supplementation may play a role in uncontrolled asthmatics with vitamin D deficiency [ 173 ].…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude of this association was the greatest in children who were vitamin D insufficient and did not receive corticosteroids [94]. By contrast, Boonpiyatad et al observed that vitamin D deficiency indeed was present in patients with asthma exacerbations but could not find a causal relationship [106]. Additionally, it was shown that children who were both vitamin D deficient and living near a major roadway were 5 times more likely to experience asthma exacerbations in comparison with children who were vitamin D sufficient and living in the same regions of high particulate matter [107].…”
Section: Vitamin D In Asthma Exacerbationmentioning
confidence: 99%